1987
DOI: 10.1177/019251218700800203
|View full text |Cite
|
Sign up to set email alerts
|

Television Coverage of Candidates' Display Behavior during the 1984 Democratic Primaries in the United States

Abstract: Analysis of network news during the 1984 presidential campaign shows that TV coverage of Democratic candidates differed in frequency and in the kinds of expressive displays shown over the course of the pre-convention period. Although political success was generally correlated with media attention, as predicted on the basis of ethology, Jackson was more successful than Mondale in becoming the unquestioned focus of news coverage. Ethological predictions of the type of display behavior shown were generally consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…19 These categories draw on research from primate and human ethology, which has found that different patterns of display behavior are associated with distinct roles in rivalry for dominance. 20,21 As composite terms, anger/threat, fear/evasion, and happiness/reassurance reflect the duality of the emotion being expressed (i.e., as expressions) and the social signals communicated (i.e., as displays). 22 Although we use these terms interchangeably, any content analysis of news coverage can only measure the visible display and can not assume the associated emotion was genuinely felt by the communicator.…”
Section: Expressive Display Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…19 These categories draw on research from primate and human ethology, which has found that different patterns of display behavior are associated with distinct roles in rivalry for dominance. 20,21 As composite terms, anger/threat, fear/evasion, and happiness/reassurance reflect the duality of the emotion being expressed (i.e., as expressions) and the social signals communicated (i.e., as displays). 22 Although we use these terms interchangeably, any content analysis of news coverage can only measure the visible display and can not assume the associated emotion was genuinely felt by the communicator.…”
Section: Expressive Display Typesmentioning
confidence: 99%
“…76 During the 1984 Democratic primaries, Mondale was more likely than his rivals to exhibit fear/evasion in his speeches and was less effective in communicating warm emotions to reinforce the support of favorably disposed viewers. 77,78 Even though he managed to win the Democratic nomination over Gary Hart and Jesse Jackson, Mondale ''failed to secure the focus of attention usually reserved for the winner [and] never successfully united the traditional Democratic constituencies.'' 79 In the general election debates with Reagan, the younger Mondale was rated as less expressive and less physically attractive than Reagan and exhibited a high rate of blinking -more than once per second, on average 80 -indicating nervousness and tension.…”
Section: The Significance Of Televised Leader Displaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In an experiment, Goethals found that Reagan's one-liners in debates helped voters see Reagan as a winner, but also important was the way he said it, his body movements, physical action, his facial expressions, or in other words, his nonverbal behaviors. Other studies showed that Mondale's facial expressions did not communicate warmth or reassurance at all to voters (Masters, Sullivan, Feola, & McHugo, 1987;Sullivan & Masters, 1988), so in effect, Mondale's nonverbal behaviors were not as good as Reagan's. In fact, nonverbal communication may be more important than the words candidates say.…”
Section: The History Of Nonverbal Communication In Political Debates mentioning
confidence: 96%